2019
DOI: 10.18203/2394-6040.ijcmph20190579
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal mapping of dengue cases in Sleman district, Indonesia year 2014-2017

Abstract: Background: Dengue is a significant public health problem in the mostly tropical country such as Indonesia. Even though many efforts have been established in Indonesia, in fact, dengue remains drawing attention from the health sector. Geographic Information System (GIS) is a powerful tool to support dengue surveillance on understanding the dengue pattern with the goal to give input for the decision maker. Accordingly, there is a need to providing the presence and the dynamic of dengue case particularly in Slem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Population density is well-known to have contributed to dengue transmission in this study. This result, in accordance with previous research in Indonesia's Sleman district, found that dengue incidence is associated with population density, and high dengue incidence has occurred in areas of high population density (51). Further, in accordance with preview studies by Arifin et al (39), Romeo-Aznar et al (52), and Nagarani et al (53), they report that unplanned population growth, mainly in the urban area, is responsible for the emergence of slum areas with insufficient sanitation that serve as mosquito breeding sites.…”
Section: Figuresupporting
confidence: 93%
“…Population density is well-known to have contributed to dengue transmission in this study. This result, in accordance with previous research in Indonesia's Sleman district, found that dengue incidence is associated with population density, and high dengue incidence has occurred in areas of high population density (51). Further, in accordance with preview studies by Arifin et al (39), Romeo-Aznar et al (52), and Nagarani et al (53), they report that unplanned population growth, mainly in the urban area, is responsible for the emergence of slum areas with insufficient sanitation that serve as mosquito breeding sites.…”
Section: Figuresupporting
confidence: 93%